Promoting the Linguistic Awareness of Teachers in Training. Case Study (2019)
Although there are several publications that have studied the importance of the Center ́s Linguistic Plan (PLC, by its Spanish acronym) as an instrument to promote the Competence in Linguistic Communication, there are not many researches that deal with the benefits of this tool to work on Linguistic awareness, although this is a fundamental issue in teacher ́s training. The objective of this article is to analyze the way we have been able to work on lin- guistic awareness through the proposal and putting into practice of the different elements that make up the didactic materials of the subject called Design and Development of a Center ́s Linguistic Plan and, very particularly, through the analysis of the one hundred  and eighteen activities carried out by forty five students of this subject in the approximate period of four months. First of all, we propose a theoretical framework in which we deal with the concepts of conscience and linguistic awareness, how to work this last one through the PLC and how it is reflected in the Infant and Primary curricula. To evaluate our objective we will present an outline of the structure of our materials in terms of contents and activities and the results of the analysis of one of the activities carried out by the students; the one we consider most significant to demonstrate that we have fostered the linguistic awareness of our students.